Optimal management of post-traumatic radioulnar synostosis - Osterman, A Lee (Orthop Res Rev, 2017)
Post-traumatic radioulnar synostosis is a rare complication after forearm or elbow injury that can result in loss of motion and significant disability. Risk factors include aspects of the initial trauma and of the surgical treatment of that trauma. Surgical intervention for synostosis is the standard of care and is determined based on the location of the bony bridge. Surgical timing is recommended between 6 months and 2 years with recent advocacy for the 6- to 12-month period after radiographs demonstrate bony maturation but early enough to prevent further stiffness and contractures. For most types of synostosis, surgical resection with interposition graft is recommended. The types of materials used include synthetic, allograft, and vascularized and non-vascularized materials, but currently there is no consensus on which is the most preferable. Adjuvant therapy is not considered necessary for all cases but can be beneficial in patients with high risk factors such as recurrence or traumatic brain injury. Postoperative rehabilitation should be performed early to maintain range of motion.